Ventilated post-mortem computed tomography – A historical review. (March 2016) - Rutty, Guy N.; Morgan, Bruno; Germerott, Tanja; Thali, Michael; Athurs, Owen
Abstract: In an attempt to improve the diagnostic quality of post-mortem computed tomography (PMCT) lung image interpretation, a series of authors have developed an approach that mimics deep inspiration and breath hold clinical thoracic CT imaging in the dead. Known as ventilated post-mortem computed tomography or VPMCT this technique has now been developed and applied to adult and paediatric PMCT imaging. This review, authored by the principal pioneers of this system, outlines the developmental stages of VPMCT, bringing the reader up to date with current knowledge and practice. Highlights: This paper reviews the development of ventilated PMCT in adults and children.